Strategi Pengembangan Agribisnis Manggis di Kecamatan Kiarapedes Kabupaten Purwakarta - Ardelia Salwa Pratiwi; Ivan Chofyan (Bandung Conference Series: Urban & Regional Planning, 2023)
Abstract.Mangosteen (Garcinia Mangostana L) is one of the leading commodities in Purwakarta District and has been recognized by the Decree of the Minister of Agriculture Number 571/KPTS/SR.120/9/2006 which states that the mangosteen fruit of Purwakarta Regency is recognized as a superior variety called Manggis Wanayasa. Kiarapedes sub-district is one of the mangosteen-producing sub-districts in Purwakarta District, which has a large potential area for developing mangosteen. In Kiarapedes sub-district, there is also mangosteen agricultural land belonging to the Food and Agriculture Service of Purwakarta District as an integrated demonstration garden. The potential possessed by Kiarapedes Sub-district has not been utilized optimally because there are still farmers who do not understand the importance of regulations and there is no advanced processing industry for mangosteen. Therefore, the purpose of this research is to determine the condition of the mangosteen commodity agribusiness in Kiarapedes Sub-district and to formulate strategies that can be implemented to support the development of mangosteen commodities in Kiarapedes Sub-district. The approach method of this research is descriptive quantitative, and the analytical method used is descriptive statistical analysis and SWOT analysis. From the results of the analysis of the condition of mangosteen agribusiness in Kiarapedes District, there are 8 internal factors, namely 4 strengths and 4 weaknesses, and 5 external factors, namely 3 opportunities and 2 threats. The mangosteen agribusiness development strategy in Kiarapedes Sub-district, especially in on farm agribusiness are in quadrant I, which is in a favorable situation, so the strategy that needs to be implemented is aggressive growth. Abstrak. Manggis (Garcinia Mangostana L) merupakan salah satu komoditas unggulan di Kabupaten Purwakarta dan telah diakui dengan adanya Keputusan Menteri Pertanian Nomor 571/KPTS/SR.120/9/2006 yang menyatakan bahwa buah manggis Kabupaten Purwakarta diakui sebagai varietas unggul yang disebut dengan Manggis Wanayasa. Kecamatan Kiarapedes merupakan salah satu kecamatan penghasil manggis di Kabupaten Purwakarta yang memiliki luas areal potensi pengembangan manggis yang masih luas, di kecamatan Kiarapedes juga terdapat lahan pertanian manggis milik Dinas Pangan dan Pertanian Kabupaten Purwakarta sebagai kebun percontohan terpadu. Potensi yang dimiliki oleh Kecamatan Kiarapedes tersebut belum dimanfaatkan secara optimal karena masih adanya perilaku petani yang belum mengerti pentingnya regulasi dan belum adanya industri pengolahan lanjutan manggis. Maka dari itu tujuan dilakukannya penelitian ini adalah untuk mengetahui kondisi agribisnis komoditas manggis di Kecamatan Kiarapedes dan merumuskan strategi yang dapat dilakukan untuk mendukung pengembangan agrbisnis manggis di Kecamatan Kiarapedes. Metode pendekatan dari penelitian ini yaitu deskriptif kuantitatif dan metode analisis yang digunakan yaitu analisis statistika deskriptif dan analisis SWOT. Dari hasil analisis kondisi agribisnis manggis di Kecamatan Kiarapedes memiliki 8 faktor internal yaitu 4 kekuatan dan 4 kelemahan, serta 5 faktor eksternal yaitu 3 peluang dan 2 ancaman. Strategi pengembangan agribisnis manggis di Kecamatan Kiarapedes khususnya pada subsistem usahatani berada pada kuadran I, yaitu berada pada situasi yang menguntungkan, sehingga strategi yang perlu diterapkan yaitu pertumbuhan agresif.